For the Sake of the Final End Eudaimonism, Self-Orientation, and the Nature of Human Agency - Darr, Ryan (2020)
The question of the viability of theological eudaimonism as an interpretation of the moral life has generated increasing debate in recent years. This essay aims to advance the debate about theological eudaimonism (and eudaimonism more generally) by addressing a closely related but insufficiently discussed issue: the nature of human agency and its relationship to value. The most commonly raised objection to eudaimonism is that it is objectionably agent-oriented. I argue that worries about objectionable self-orientation often stem from importing foreign pictures of agency into the eudaimonist tradition. I make this case through an analysis of Nicholas Wolterstorff’s recent critique of eudaimonism. Wolterstorff presupposes a common contemporary conception of agency. Drawing on Thomas Aquinas and Elizabeth Anderson, I show that other conceptions of agency are available. Clarity about the nature of human agency and its relationship to value will bring greater clarity to the debate about eudaimonism and self-orientation.
Keywords: Elizabeth Anderson; Nicholas Wolterstorff; Thomas Aquinas; Agency; Eudaimonism; final end; Happiness; self-orientation